2022
DOI: 10.1007/s00127-022-02390-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in suicide, suicidal ideation, and self-harm after release from incarceration: a systematic review and meta-analysis

Abstract: Purpose People released from incarceration are at increased risk of suicide compared to the general population. We aimed to synthesise evidence on the incidence of and sex differences in suicide, suicidal ideation, and self-harm after release from incarceration. Methods We searched MEDLINE, EMBASE, PsycINFO, Web of Science and PubMed between 1 January 1970 and 14 October 2021 for suicide, suicidal ideation, and self-harm after release from incarceration (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 104 publications
0
14
0
1
Order By: Relevance
“…The number of postrelease suicides equaled the released person count times the CMR. The study sets comprised (1) our primary estimate; (2) a study from Ontario, Canada 17 ; (3) the SMR for releases in England and Wales 23 ; (4) a consolidated estimate from separate computations by sex; and (5) the meta-analysis by Janca et al 5 First, we estimated suicide SMRs in postrelease years 1 and 2 using meta-analytic RE-ML pooling of SMRs from 10 jurisdictions. Variance for CMRs and SMRs were computed using standard formulas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of postrelease suicides equaled the released person count times the CMR. The study sets comprised (1) our primary estimate; (2) a study from Ontario, Canada 17 ; (3) the SMR for releases in England and Wales 23 ; (4) a consolidated estimate from separate computations by sex; and (5) the meta-analysis by Janca et al 5 First, we estimated suicide SMRs in postrelease years 1 and 2 using meta-analytic RE-ML pooling of SMRs from 10 jurisdictions. Variance for CMRs and SMRs were computed using standard formulas.…”
Section: Discussionmentioning
confidence: 99%
“…3 Growing global literature suggests an even higher suicide rate in the year after release from incarceration; meaning that more suicides per day occur after release than during jail time. 4,5 Only 1 study with high-quality death registration, however, is specific to US jails: among Philadelphia Medicaid beneficiaries who died by suicide between 2003 and 2018, 25% had a history of Philadelphia county jail incarceration. 6 In the US, no data exist on suicide risk during an actionable period of 1 to 2 years after jail release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, most research on suicide risk in prison is developed in male samples (Dye, 2011), even though previous literature has established that women present a higher number of risk factors (Spjeldnes et al , 2014). Indeed, a recent systematic review and meta-analysis showed that, even though the prevalence of suicide in general population tends to be higher in men, this difference does not exist between male and female prisoners (Janca et al , 2023). Taking into account the aspects mentioned above, we consider that the validation of such instrument is particularly relevant as it provides a reliable tool that allows a brief screening of both men and women who might report concerns that could predict future risk of suicide even though they do not show suicidal intention at that moment.…”
Section: Introductionmentioning
confidence: 99%
“…Так, членовредительство является основной причиной заболеваемости среди заключённых [2]. Люди, освобождённые из мест лишения свободы, подвержены повышенному (в семь раз выше) риску самоубийства [3], а шансы умереть от насилия у них в восемь раз больше, чем у населения в целом [4]. При этом особо высокие показатели различных самоповреждений наблюдается как раз среди убийц [5,6].…”
unclassified